Fetal growth in different racial groups. Issue 1 (January 1978) - Alvear, J; Brooke, O G
Abstract : Three racial groups of mothers and their newborn babies– North European 75, Negro 75, and "Indian" Asian 37–were matched for parity, gestational age, sex, maternal age, maternal smoking habits, and social class. Multiple anthropometric measurements, including skinfold thickness, limb circumferences, and various linear measurements were made on the mothers and their infants to determine the effects of race and smoking on fetal size. Indian-Asian mothers, though shorter and lighter than Europeans and Negroes, had similar skinfold thickness and weight: height2 ratios and gained as much weight during pregnancy. Their infants, however, were lighter than the others, and had smaller head and limb circumferences, although their linear measurements were the same. Negro and European infants were almost identical in size. We found no effect on any of the fetal measurements which could be attributed to smoking.